TIPS under-dilation strategy with new controlled expansion endoprosthesis: A hemodynamic and imaging confirmation of its feasibility. (March 2023) - Saltini, D.; Caporali, C.; Indulti, F.; Casari, F.; Prampolini, F.; Felaco, D.; Battinelli, G.; Bianchini, M.; Guasconi, T.; Cuffari, B.; Zanetto, A.; Olivieri, T.; et al.
Abstract : Introduction: The use of small caliber (<8 mm) transjugular intrahepatic portosystemic shunt (TIPS) is a promising approach to reduce shunt-related complications. Its feasibility with the new controlled expansion endoprosthesis (GORE® VIATORR® CX 8-10 mm) has not yet been explored. Aim: To investigate whether GORE® VIATORR® CX self-expands over time at portal vein wall (PVW) and hepatic vein wall (HVW) when under-dilated to <8 mm at TIPS placement. Material & Methods: We prospectively enrolled consecutive patients with cirrhosis who received under-dilated TIPS between June 2020 and September 2022 at our tertiary referral Center in Modena, Italy. All patients underwent hemodynamic measurements a) immediately before and after TIPS placement, b) 6-7 days and c) ≥1 month after the procedure. We measured average pressure values in different sites along the TIPS: portal-vein tract (PV), intra-parenchymal tract (IP), hepatic-vein tract (HV) and inferior vena cava (IVC). A subgroup of patients underwent serial CT scans within 24h (T0), at 6-7 days (T1) and at ≥1 month after TIPS (T2). Average maximal inner diameter of endoprosthesis was measured at 5 standard sites: PV, PVW, IP, HVW and distal HV. Results: Sixty-four patients underwent hemodynamic assessments: 25, 29 and 10 received TIPS under-dilated to 5, 6 and 7 mm, respectively. A significant drop of pressure was observed while crossing PVW and HVW in all under-dilated groups (Figure 1A). Forty-three of these patients underwent CT scans: 17, 19 and 7 were dilated to 5, 6 and 7 mm, respectively. PVW and HVW sites maintained under-dilation overtime (Figure 1B). No TIPS dysfunction occurred during a mean follow up period of 363 days. Conclusion: Under-dilation TIPS strategy performed with GORE® VIATORR® CX is feasible. Evaluation of clinical outcomes after applying this strategy are awaited.